The role of mindfulness in improving concentration and performance among players in the Iraqi second division football league - Ahmed Jalal Ibrahim (Khatulistwa Education Center, 2026)
Background Attention to the psychological aspect of players has become an essential part of sports preparation programs, as many studies indicate that psychological abilities such as concentration, attention, and emotional control play an important role in achieving athletic accomplishment, especially in team sports such as football, which are characterized by rapid performance and multiple changing situations during the match. Objectives The research aims to identify the role of mindfulness in improving concentration and sports attention among football players. Methods The researcher used the descriptive method due to its suitability to the nature of the research. The research sample consisted of (37) football players, To collect data, the researcher used a mindfulness scale and a sports concentration and attention scale, after verifying their validity and reliability. The analysis in this study was assisted using the SPSS 26 application. Results The results of the study showed that the dimension of attention to the present moment ranked first among the dimensions of mindfulness, with an agreement percentage of (80.88%), followed by the dimension of attention control with (73.71%), while the dimensions of awareness of feelings and thoughts and body awareness during performance recorded moderate percentages,The results also showed that the dimension of attention shifting ranked first among the dimensions of sports concentration and attention with (91.50%), followed by the dimension of response speed to stimuli with (82.42%). Conclusion The results further revealed the existence of statistically significant positive correlations between the dimensions of the mindfulness scale and the dimensions of the sports concentration and attention scale among football players. This indicates that the higher the level of mindfulness among players, the higher their level of concentration and attention during sports performance,In light of these results, the researcher recommended the importance of developing mindfulness skills among football players and incorporating them into psychological preparation programs, due to their important role in improving concentration, attention, and sports performance.